Decoding pituitary tumors: a systematic analysis of diagnostic methods and treatment modalities - Bandari, Pruthvi; R. K., Rosheni; Gowda, Medhini H.; Anwitha, Gangineni Sri Sai; M., Kumaraswamy; K. S., Surabhi (International Journal of Research in Medical Sciences, 2024)
Pituitary tumors are growths that form in the gland these tumors are rare representing 10-15% of all brain tumors. They can disrupt the production of hormones, in the body leading to symptoms related to hormone imbalance. This review offers an overview of the methods used for diagnosing and treating tumors. It is worth noting that relying solely on references may restrict the scope and depth of discussions about tumors in this paper. Suggestions for research include exploring diagnostic tools like molecular imaging and liquid biopsy to enhance early detection and accurate assessment of these tumors. Additionally, more research is required to understand the long-term effects and quality of life outcomes for patients undergoing treatment options for tumors. In conclusion, significant progress has been made in diagnosing and treating tumors over time. Advances in imaging technologies such as diffusion-weighted imaging and magnetic resonance spectroscopy have enhanced precision and treatment strategies for these tumors. The discussion also covers the roles of surgery, radiation therapy and medical interventions, in managing tumor growth and hormonal imbalances further advancements, in research and innovation are crucial, for enhancing our knowledge and treatment of tumors ultimately bringing outcomes for both patients and healthcare professionals.